Can Kālidāsa’s Poetic Vision Be Read as a Mīmāṃsā–Vedānta Continuum from Dharma to Brahman? - Aggarwal, Shradha (जम्बूद्वीप - the e-Journal of Indic Studies (ISSN: 2583-6331), 2026)
Classical Indian philosophy frequently presents Pūrva-Mīmāṃsā and Vedānta as distinct—if not opposed—darśanas, one centred on dharma and ritual action (karma), and the other on metaphysical knowledge (jñāna) and liberation (mokṣa). This paper argues that Kālidāsa’s poetic vision reflects neither rigid opposition nor doctrinal synthesis, but rather a continuum in which dharma, understood as lived, embodied, and ethically meaningful action, gradually matures into inward awareness and metaphysical insight. Drawing upon foundational Mīmāṃsā concepts such as codanā, pravṛtti, and apūrva, alongside Vedāntic notions of ātman, brahman, and anubhava, the study offers a sustained darśanic reading of Kālidāsa’s major works—Raghuvaṃśa, Kumārasambhava, Abhijñānaśākuntalam, and Meghadūta. Through close textual analysis with aligned Sanskrit citations (IAST and translation), the paper demonstrates that Kālidāsa presents action as ethically and aesthetically transformative rather than merely ritualistic, while simultaneously gesturing toward a Vedāntic horizon of self-recognition and non-dual awareness. Kālidāsa thus emerges as a philosopher-poet within the Indian Knowledge Tradition, articulating a non-polemical vision in which karma and jñāna coexist in continuity rather than opposition.